A Lightweight and Interpretable Recurrent Vision Transformer for Robust Potato Blight Classification - Prakash Sandhya; B Venkataramana (Potato Research, 2026)

Genetic and genomic resources of Vigna species for their utility in advanced breeding - Kuldeep Kumar; Sudhir Kumar Jha; B. Manu; Adarsh Kumar; Vaibhav Kumar; Khela Ram Soren; Meenal Rathore; Sandhya Sharma; Kishor Gaikwad (Biologia Futura, 2026)

Enhanced Delivery of Methotrexate for Scalp Psoriasis Treatment via Nanosuspension Hair Dye: A Box-Behnken Optimization Approach - Poojitha P.N.; Akhil Perumalla; Sandhya Rachamalla; shirisha Mandli; Shilpa Ajje; Sindura Talari; Shaik Afroz Kottapalli; Nagashubha B; M. Kiran Sai (Journal of Pharmaceutical Innovation, 2025)

Delving into the BURP Super family: A Comprehensive QTL-Assisted Study on RD22 genes and its Role in Salinity Stress Tolerance in Chickpea - Sandhya Tripathi; Chellapilla Bharadwaj; Maloti Hembram; Neeraj Kumar; Aravind K. Konda; B. Mondal; N. C. Gupta; G. P. Dixit; K. R. Soren (Biochemical Genetics, 2025)

Semi-synthetic ecdysteroids as promising new antichagasic agents - Márton B. Háznagy; Máté Vágvölgyi; Sandhya R. Krishnan; Kaushavi Cholke; Jürg Gertsch; Attila Hunyadi (Phytochemistry Letters, 2025)

SK609, a novel dopamine D3 receptor agonist and norepinephrine transporter blocker with putative pro-cognitive actions, does not induce psychostimulant-like increases in risky choice during probabilistic discounting - Christopher P. Knapp; Brooke Fallon; Sandhya Kortagere; Barry D. Waterhouse; Stan B. Floresco; Rachel L. Navarra (Psychopharmacology, 2025)
Rationale Psychostimulants, such as amphetamine (AMPH) and methylphenidate (MPH), non-selectively elevate extracellular concentrations of the catecholamine neurotransmitters, dopamine (DA) and norepinephrine (NE), and are common pharmacological strategies used to improve prefrontal cortex (PFC)-dependent cognitive dysfunction. However, this approach can be problematic given AMPH has been shown to increase preference for risky choices in a rodent assay of risk/reward decision making. SK609 is a novel NE reuptake blocker that selectively activates DA D3 receptors without affinity for the DA transporter. SK609 has been shown to improve cognitive performance without increasing psychostimulant-like spontaneous locomotor activity, suggesting SK609 may benefit neurocognitive function without psychostimulant-like side effect liability. Objectives We compared AMPH, MPH, and SK609 within dose ranges that display their cognitive enhancing properties in a probabilistic discounting task (PDT) of risk/reward decision making behavior to assess their potential to increase risky choice preference. Methods Rats chose between small/certain rewards delivered with 100% certainty and large/risky rewards delivered with descending probabilities across a session (100 − 6.25%) following administration of AMPH (0.25-1 mg/kg), MPH (2–8 mg/kg), and SK609 (4 mg/kg). Results AMPH and MPH increased risky choice behavior at doses previously reported to enhance cognition, whereas SK609 did not. AMPH and MPH also reduced sensitivity to non-rewarded risky choices. Conclusions These data highlight the combination of NE transporter blockade and selective D3 activation in pro-cognitive action without psychostimulant-like side effect liability. The absence of DA transporter blockade and non-selective dopaminergic activation are beneficial properties of SK609 that differentiates it from the traditional pro-cognitive psychostimulants.

Marine Life Ecosystem Analysis Based on Climate Change Detection Using Deep Learning Algorithms - B. Rebecca; A. Sandhya; Kiran Sree Pokkuluri; Gunipati Kanishka; Khasimbee Shaik; B. Murali Krishna (Remote Sensing in Earth Systems Sciences, 2025)

Dual Metal Ion Sensing by an Azo Compound Derived from Thiazolo[3,2-a] Indole: A Selective and Sensitive Approach - Haitham K.R. Al-Sharifi; C. B. Meenakshy; K. S. Sandhya; Ani Deepthi (Journal of Fluorescence, 2025)

Hydrochemical Evaluation of Groundwater Quality and Human Health Risk Assessment of Fluoride and Nitrate: A Case Study of Pratapgarh District UP, India - Sandhya Maurya; Ashok B. More; Garima Gupta; Abhishek Saxena; Anjali Singh (Water, Air, & Soil Pollution, 2025)

Proteomic Characterization of Human Placenta: Insights into Potential Therapeutic Applications for Osteoarthritis - Jithu Jerin James; K. V. Sandhya; K. N. Sridhar; S. Sudarson; B. V. Basavaraj; S. Bharath (AAPS PharmSciTech, 2024)

Wastewater-Based Epidemiology of SARS-CoV-2: Assessing Prevalence and Correlation with Clinical Cases - Hima Wani; Smita Menon; Dipen Desai; Nishita D’Souza; Zarine Bhathena; Nishith Desai; Joan B. Rose; Sandhya Shrivastava (Food and Environmental Virology, 2023)

Population genetic research on the Spadenose shark, Scoliodon laticaudus (Chondrichthyes, Carcharhinidae), reveals the presence of two significantly differentiated clades along the Indian coast - Sandhya Sukumaran; Wilson Sebastian; P. U. Zacharia; Shoba J. Kizhakudan; K. V. Akhilesh; Sujitha Thomas; Subal Kumar Roul; M. Muktha; Swati Priyanka Sen; G. B. Purushottama; Shikha Rahangdale; K. K. Bineesh; et al. (Marine Biodiversity, 2023)

Determining the presence of glyphosate and glyphosate-tolerant events in maize and soybean food products in South Africa - Christopher D. Viljoen; B. J. Koortzen; Sandhya Sreenivasan Tantuan (Food Additives & Contaminants Part B-Surveillance, 2021)

Status of Hilsa Fishery in Hooghly-Bhagirathi River System and Associated Coastal Waters of Northern Bay of Bengal - A. M. Sajina; V. R. Suresh; K. M. Sandhya; J. Mukherjee; R. K. Manna; B. K. Behera; R. Samanta; T. Maity; S. K. Banik (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Antibacterial and biofilm inhibition activity of biofabricated silver nanoparticles against Xanthomonas oryzae pv. oryzae causing blight disease of rice instigates disease suppression - Sandhya Mishra; Xiaodong Yang; Shatrupa Ray; Leonardo Fernandes Fraceto; H. B. Singh (World Journal of Microbiology and Biotechnology, 2020)

Rational Design, Synthesis, and In Vitro Neuroprotective Evaluation of Novel Glitazones for PGC-1α Activation via PPAR-γ: a New Therapeutic Strategy for Neurodegenerative Disorders - Antony Justin; Subhankar Mandal; P. Prabitha; S. Dhivya; S. Yuvaraj; Pradeep Kabadi; Satheesh John Sekhar; C. H. Sandhya; Ashish D. Wadhwani; Selvaraj Divakar; Jeyabalan Jeyaram Bharathi; Priya Durai; et al. (Neurotoxicity Research, 2020)

Modeling the effect of sanitation in a human habitat to control the spread of bacterial diseases - J. B. Shukla; Ram Naresh; Sandhya Rani Verma; Manju Agarwal (Modeling Earth Systems and Environment, 2020)

pH as a proxy for estimating plant-available Si? A case study in rice fields in Karnataka (South India) - Jean-Dominique Meunier; Kollalu Sandhya; Nagabovanalli B. Prakash; Daniel Borschneck; Philippe Dussouillez (Plant and Soil, 2018)

Status, Prospects, Threats, and the Way Forward for Sustainable Management and Enhancement of the Tropical Indian Reservoir Fisheries: An Overview - U. K. Sarkar; K. M. Sandhya; P. Mishal; G. Karnatak; S. Kumari; P. Panikkar; R. Palaniswamy; M. Karthikeyan; S. Sibina Mol; T. T. Paul; V. L. Ramya; D. S. K. Rao; et al. (Reviews in Fisheries Science & Aquaculture, 2018)

Origin of silica in rice plants and contribution of diatom Earth fertilization: insights from isotopic Si mass balance in a paddy field - Jean Riotte; Kollalu Sandhya; Nagabovanalli B. Prakash; Stéphane Audry; Thomas Zambardi; Jérôme Chmeleff; Sriramulu Buvaneshwari; Jean-Dominique Meunier (Plant and Soil, 2018)

Fluorescence Quenching Property of C-Phycocyanin from Spirulina platensis and its Binding Efficacy with Viable Cell Components - Meenakshi B. Paswan; Meghna M. Chudasama; Madhusree Mitra; Khushbu Bhayani; Basil George; Shruti Chatterjee; Sandhya Mishra (Journal of Fluorescence, 2016)

Diurnal variations of the low-level jet over peninsular India during the onset of Asian summer monsoon - Sandhya K. Nair; Thara V. Prabha; N. Purushothaman; S. Sijikumar; S. Muralidharan; N. V. P. Kirankumar; D. B. Subrahamanyam; T. J. Anurose; S. S. Prijith; K. V. S. Namboodiri (Theoretical and Applied Climatology, 2015)

Elucidation of binding mechanism and identification of binding site for an anti HIV drug, stavudine on human blood proteins - B. Sandhya; Ashwini H. Hegde; J. Seetharamappa (Molecular Biology Reports, 2013)

Estimation of variables explaining urbanization concomitant with land-use change: a spatial approach - G. Sandhya Kiran; Usha B. Joshi (International Journal of Remote Sensing, 2013)

Interaction of fishes with pathogenic micro-organisms and application of phages for their control: a review - Swapnil G. Sanmukh; Dilip B. Meshram; Waman N. Paunikar; Sandhya Swaminathan (Reviews in Fish Biology and Fisheries, 2012)

Vertical structure of sea-breeze circulation over Thumba (8.5°N, 76.9°E, India) in the winter months and a case study during W-ICARB field experiment - T. J. Anurose; D. Bala Subrahamanyam; C. B. S. Dutt; N. V. P. Kiran Kumar; Sherine Rachel John; Sandhya K. Nair; M. Santosh; Mannil Mohan; P. K. Kunhikrishnan; S. Sijikumar; S. S. Prijith (Meteorology and Atmospheric Physics, 2012)

Evaluation of binding and thermodynamic characteristics of interactions between a citrus flavonoid hesperitin with protein and effects of metal ions on binding - Ashwini H. Hegde; B. Sandhya; J. Seetharamappa (Molecular Biology Reports, 2011)

Cajanus platycarpus (Benth.) Maesen as the donor of new pigeonpea cytoplasmic male sterile (CMS) system - Nalini Mallikarjuna; Deepak R. Jadhav; Sandhya Srikanth; Kulbhushan B. Saxena (Euphytica, 2011)

Role of microorganisms in adaptation of agriculture crops to abiotic stresses - Minakshi Grover; Sk. Z. Ali; V. Sandhya; Abdul Rasul; B. Venkateswarlu (World Journal of Microbiology and Biotechnology, 2011)

Effect of osmotic stress on plant growth promoting Pseudomonas spp. - V. Sandhya; Sk. Z. Ali; B. Venkateswarlu; Gopal Reddy; Minakshi Grover (Archives of Microbiology, 2010)

Agrobacterium-Mediated Transformation of cry1Ac Gene into Shoot-Tip Meristem of Diploid Cotton Gossypium arboreum cv. RG8 and Regeneration of Transgenic Plants - S. B. Nandeshwar; Sandhya Moghe; P. K. Chakrabarty; M. K. Deshattiwar; Keshav Kranthi; P. Anandkumar; C. D. Mayee; B. M. Khadi (Plant Molecular Biology Reporter, 2009)

Pseudomonas sp. strain AKM-P6 enhances tolerance of sorghum seedlings to elevated temperatures - Sk. Z. Ali; V. Sandhya; Minakshi Grover; N. Kishore; L. Venkateswar Rao; B. Venkateswarlu (Biology and Fertility of Soils, 2009)

Alleviation of drought stress effects in sunflower seedlings by the exopolysaccharides producing Pseudomonas putida strain GAP-P45 - V. Sandhya; Ali SK. Z.; Minakshi Grover; Gopal Reddy; B. Venkateswarlu (Biology and Fertility of Soils, 2009)

ProRegIn: A regularity index for the selection of native-like tertiary structures of proteins - Lipi Thukral; Sandhya R Shenoy; Kumkum Bhushan; B Jayaram (Journal of Biosciences, 2007)

Effect of Sub-Lethal Concentrations of Endosulfan on Hematological and Serum Biochemical Parameters in the Carp Cyprinus carpio - F. Jenkins; J. Smith; B. Rajanna; U. Shameem; K. Umadevi; V. Sandhya; R. Madhavi (Bulletin of Environmental Contamination and Toxicology, 2003)